PENGGUNAAN TEPUNG BUAH MENGKUDU (MORINDA CITRIFOLIA) UNTUK MENINGKATKAN KUALITAS PAKAN AYAM RAS - Imbang Dwi Rahayu, Asmah Hidayati, (Jurnal Gamma, 2006)
The objective of this research was to know the mengkudu meal as natural feed aditif for quality increase of layer ration especially is dry matter, organic matter and mineral; nitrogen balance and biologis digestibility of ration. The material was used in this experiment five teen layer hens, in eighteen months old, devide into five groups treatment namely P0 (0%), P1 (0,5%), P2 (1,0%), P3 (1,5%) and P4 (2,0%) of mengkudu meal in ration. Individual cages and force feeding methods for used in this treatment. The quality of ration and nutrient in feces was analyzed by procsimat (AOAC, 1996). The result of this research: mengkudu meal as natural feed aditif have effect not significan't for quality increase of layer ration. Based on value of each variable on quality ration, mengkudu meal give quality increase up to 1,5% added in ration; and it was decrease total price of ration.